Conversion of Valence State and Coordination State of Fe in Transparent Glass‐Ceramics Containing Li2ZnSiO4 Nanocrystals. Issue 9 (20th May 2013) - Zhuang, Yixi; Tanabe, Setsuhisa; Pickney, L.
<x xml:space="preserve">Abstract</x> Transparent glass‐ceramics containing Li2ZnSiO4:Fe nanocrystals were prepared by melt‐quenching method followed by post‐heat‐treatment process. The as‐prepared glasses and glass‐ceramics showed red to near‐infrared photoluminescence centered at 730 nm, ascribed to Fe3+ ions in tetrahedral coordination. The intensity of the photoluminescence was enhanced by two technologically simple techniques—the valence state of irons was controlled from Fe2+ to Fe3+ ions using oxidizing agents, whereas the coordination state was compulsorily converted from octahedral to tetrahedral symmetry by performing a ceramization process. The presence of Fe2+ ions was considered a major origin for Fe3+ photoluminescence quenching. Oxidation of Fe2+ and conversion of Fe2+ ions into tetrahedral symmetry contribute to suppression of energy transfer from Fe3+ emitters to Fe2+ quenching centers.